International background of Pedagogy of death - Pablo Rodríguez Herrero; Agustín De la Herrán Gascón; Mar Cortina Selva (FahrenHouse, 2019)
Death is a universal and perennial phenomenon for the human being. Nevertheless, the pedagogy of death is a taboo subject in schools. It has not become aware of its formative value. Research and proposals are isolated, although they articulate an important theoretical and practical basis for developing a possible pedagogy of death. This article presents a theoretical review of the international history of the pedagogy of death. Articles published in scientific impact journals, education magazines, doctoral theses, books, book chapters, as well as conferences, communications and presentations at scientific conferences or journals have been reviewed. The purpose is to present a comprehensive review of interest to researchers and teachers addressing the issue of death in education. The classification of the analyzed works is made concrete in the following categories: a) Work carried out in the normalization of the death in the education; and b) Works focused on educational intervention palliative or post-significant loss. The conclusions reflect on the lines of innovation and research priority to normalize death in the educational field. Among them, it highlights the possible contribution of the pedagogy of death in the educational response to the great challenges of today's society.